World antidoping system design deficiencies and key contradictions with Olympic tenets - Lidov, P. I.; Kurbatskaya, A. A.; Sukhanovsky, Y. A.; Kaziakhmetov, A. M.; Vorobyev, A. I. (Theory and Practice of Physical Culture, 2017)
The article analyses progress of the global antidoping system on the whole and WADA in particular to demonstrate the ideological errors made in its design stage and echoed in the presently unfair structure and policies of the Agency. The geocentric design of the WADA makes it possible for the majority nations to effectively lobby their interests in fact. This initial structural distortions further aggravated by the biased practical activities of the WADA largely determined by the vested interests of a few leading nations have resulted in a deep crisis of the global antidoping system, its irreconcilable conflict with the Olympic Charter and a serious threat for the global Olympic movement on the whole - since the economic and political factors of the WADA establishment and operations make it susceptible to political and other pressures in violation of the Olympic principles of equality, integrity and unbiased attitudes - still supported and advanced by the International Olympic Committee.